Clean code applied building a Java web application with software craftmanship - Martin, Robert C. (Addison-Wesley Professional, 2017)
Even bad code can function. But if code isn't clean, it can bring a development organization to its knees. Robert C. Martin and Micah Martin reveal the disciplines, techniques, tools, and practices that separate software craftsmen from mere "9-to-5" programmers.--Includes text from resource description page.
Title from resource description page (Safari, viewed June 26, 2017)
Keywords: Agile software development; Computer software -- Development; Computer software -- Reliability; Méthodes agiles (Développement de logiciels); Logiciels; Fiabilité; Computer software; Development; Computer software; Reliability